Professional Turkish soccer players' perception towards different teaching methods - Yoncalik, O. (Facta Universitatis: Series Physical Education and Sport, 2010)
The results of this research have shown that the educational level of soccer players did not cause a difference in their perceptions of the different teaching methods used by their coaches during training sessions. According to the results of the analyses that aimed to reveal the common viewpoints of 157 professional soccer players, members of eight different teams of the 1st and the 2nd Turkish Professional Soccer League, who participated in the research, the coaches mostly prefer the "command style" during the trainings. The soccer players, perceived no differences among the teaching approaches called "practice", "command" and "discovery" as strong education approaches, in terms of their effectiveness in technical tactic and other exercises during the trainings. The soccer players listed the strongest education approaches that could motivate them for trainings techniques such as "command", "discovery" and "practice" styles, respectively. The results also demonstrate that the primary style that can turn the training sessions into pleasant activities is "discovery". From this respect, "practice" follows the "discovery" style.